2019
DOI: 10.5771/1435-2869-2019-1-117
|View full text |Cite
|
Sign up to set email alerts
|

The gender pay gap in North Macedonia: Assessing the difference between low-paid and high-paid employees

Abstract: The labour market in North Macedonia is characterised by strong differences in terms of the vertical distribution of jobs and the higher probability of women being in low-paid and unpaid family jobs. Data from the EU-level Survey on Income and Living Conditions show that women are much more likely to be low-paid, while estimations of the earnings function indicates a significant gender pay gap and the potential for discrimination in the labour market against women. From a policy perspective, this article ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
2
1
Order By: Relevance
“…The qualitative research approach can also address the such phenomenon, revealing what kind of family or household situations are more likely associated with higher earnings. Another research opportunity is hidden in the role of discrimination and diversity, which was suggested as important in recent studies, but was not found significant within our analysis (Nikoloski et al 2018(Nikoloski et al , Černušáková 2021. Despite this non-finding, the study joins the up-to-date research debate, asking whether individual perceptions and attitudes to the various ethnicities and nationalities can be translated into higher/lower earnings, conditioned to the other factors and variables unchanged.…”
Section: Research Sample and Variablescontrasting
confidence: 51%
See 1 more Smart Citation
“…The qualitative research approach can also address the such phenomenon, revealing what kind of family or household situations are more likely associated with higher earnings. Another research opportunity is hidden in the role of discrimination and diversity, which was suggested as important in recent studies, but was not found significant within our analysis (Nikoloski et al 2018(Nikoloski et al , Černušáková 2021. Despite this non-finding, the study joins the up-to-date research debate, asking whether individual perceptions and attitudes to the various ethnicities and nationalities can be translated into higher/lower earnings, conditioned to the other factors and variables unchanged.…”
Section: Research Sample and Variablescontrasting
confidence: 51%
“…Empirical researchers have expanded the original equation of schooling and experience by including other relevant factors impacting earnings and testing their empirical validity (Angrist andKrueger 1991, Mincer 1997). The Mincer equation function was thus used to study the role of basic individual characteristics, including age (Bhuler et al 2017), ethnicity and nationality (García-Aracil and Winter 2006), gender pay gap (Hedija 2017), sexual orientation (Martell 2019), discrimination and disability (Nikoloski et al 2018). However, also the role of family status, children and household characteristics (Chiswick 2003), and living region (Beenstock and Felsenstein 2008).…”
Section: Introductionmentioning
confidence: 99%
“…After he published his work, many estimations of his earnings function have been developed and multiplied all around the world. For instance, in the USA (Andini, 2013), in India (Geetha Rani, 2014), in Colombia (García-Suaza et al , 2014), in Turkey (Cankal and Gokce, 2015), in The Netherlands (Hartog and Gerritsen, 2016), in Germany (Humpert, 2016), in Macedonia (Nikoloski et al , 2018) and in many other countries. A compilation of these studies can be found in Heckman et al (2003) and Lemieux (2006).…”
Section: Introductionmentioning
confidence: 99%